Implementation of Agent Based Modelling to Observe the Evacuating Behavior at Faculty of Engineering Building, University of Bengkulu, Indonesia - Hardiansyah; Wida Fitrianip; Annisa Fitria Edriani; Robi Hardiansyah; Rizka Lestyanti; Lindung Zalbuin Mase (Journal of the Civil Engineering Forum, 2022)
Evacuation is an important issue during the occurrence of an earthquake, due to the influence of people’s responsive behaviours to the disaster. This indicates the occurrence of overcrowded conditions, which causes the conflict of people’s movement. It is also one of the main reasons the process of evacuation is difficult, leading to the necessity to specifically model the movement within each building. Therefore, this study aims to analyze the earthquake evacuation modelling in Faculty of Engineering building, University of Bengkulu, Indonesia. This used a multi-agent programmable modelling environment known as NetLogo, which adopted an ABM model that is often utilized to observe elemental movement response. The agents occupying the building also moved to the stairs and evacuation doors, for exit towards the assembly point, which was located in front and behind Faculty of Engineering. The agent-based modelling is then conducted by inputting the layout of the building and the number of occupants in each room. Furthermore, the simulations were performed by considering various agents’ capacity in the building, during the evacuation. The results showed the time taken for the agents to exit the building during the disaster. This confirmed that the required exit time generally decreased with the increasing population percentage in the building. During this process, the conflict point also occurred around the corridor of Floors 1 and 2 (T1, T2 and T3), as well as the exits of the building (P1, P2, P3, and P4). This was due to the occurrence of a high density when agents carry out evacuation movements. Based on these results, the placement of signs was recommended, as guidelines during the evacuation process.